The elasticity of substitution between native and immigrant labor: A meta-analysis - Klara Kantova; Tomáš Havránek; Zuzana Havránková (Charles University in Prague, Institute of Economic Studies (IES), 2025)
This paper presents the first comprehensive meta-analysis of the elasticity of substitution between native and immigrant labor. Drawing on 1,091 estimates from 41 studies, we examine whether immigrants and natives compete in the same labor markets, and to what extent published estimates are shaped by methodological choices and publication bias. We find strong evidence of small-study effects: less precise estimates are associated with lower elasticities, which is consistent with selective reporting. Correcting for these biases using a wide array of techniques (linear, nonlinear, and selection models) raises the mean implied elasticity from 13 to approximately 20. Model averaging techniques reveal that data features, such as experience level, wage definition, and region, explain much of the heterogeneity in reported results. Notably, the often-cited discrepancy between using log(mean wages) and mean(log wages) largely disappears once publication bias is accounted for. Our findings imply that immigrants and natives are imperfect substitutes but more substitutable than is commonly assumed.
Keywords: J15; J61; C83; 330; elasticity of substitution; immigration; native labor; metaanalysis; publication bias